1983
DOI: 10.1159/000221562
|View full text |Cite
|
Sign up to set email alerts
|

Peripher-venöse hypokalorische Ernährung nach großen Abdommaleingriffen

Abstract: In einer Pilotstudie wurde bei 10 Patienten nach großen abdominal-chirurgischen Eingriffen, wie Gastrektomie und Ösophagektomie, eine peripher-venöse hypokalorische Ernährung über 10 Tage durchgeführt. Aufnahmekriterien waren ein guter Ernährungszustand nach anthropometrisch und laborchemischen Kriterien und ein komplikationsloser Eingriff mit einer Operationszeit unter 4 Stunden und maximal 1000 ml Blutverlust. Nach 8- bis lOtägiger Infusionszeit lagen die Meßgrößen (Armumfang, Albumin, Präalbumin, Transferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our opinion, the duration of hypocaloric nutrition should be limited to the first 4-5 postoperative days, depending on the acute and maximal hormonal reaction to trauma. Nonetheless, a longer postoperative hypocaloric nutrition did not basically compare unfavorably after 8--10 days with a conventional higher caloric postoperative parenteral nutrition [43].…”
Section: Practical Applicationmentioning
confidence: 88%
“…In our opinion, the duration of hypocaloric nutrition should be limited to the first 4-5 postoperative days, depending on the acute and maximal hormonal reaction to trauma. Nonetheless, a longer postoperative hypocaloric nutrition did not basically compare unfavorably after 8--10 days with a conventional higher caloric postoperative parenteral nutrition [43].…”
Section: Practical Applicationmentioning
confidence: 88%
“…Recent studies have demonstrated the postoperative caloric requirements to be lower than formerly assumed [2]. Investigation of postoperative metabolism led to new nutritional concepts, namely, the hypocaloric protein-sparing therapy and the lipid system both being peripheral venous nutritive regimens [3][4][5][6][7]. When a decision must be made whether peripheral or central venous nutrition is adequate, not only the caloric requirement and the metabolic situation but also advantages and disadvantages of the access routes should be considered.…”
mentioning
confidence: 99%